Parallel lines or divergent trajectories? A response to the other contributions - Keep, E (Routledge, 2019)
This article provides a response to the other contributions in this special issue and explores the range and scale of the opportunities for policy learning across the four UK nations. It addresses the importance of locating FE and skills policy within wider national policy contexts, national choices between markets and systems and the wider implications of these choices, and the vexed role of employers. Behind these lie three over-arching questions that are then interrogated – have we arrived at a moment when we can conceive of the UK as a policy learning laboratory, is this laboratory open for expansive policy learning, and who might be working in it?